2009
DOI: 10.1007/s10508-009-9499-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodemographic and Physical Correlates of Sexual Orientation in Men

Abstract: To better understand sexual orientation from an evolutionary perspective, we investigated whether, compared to heterosexual men, the fewer direct descendants of homosexual men could be counterbalanced by a larger number of other close biological relatives. We also investigated the extent to which three patterns generally studied separately--handedness, number of biological older brothers, and hair-whorl rotation pattern--correlated with each other, and for evidence of replication of previous findings on how ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(101 citation statements)
references
References 71 publications
8
90
1
1
Order By: Relevance
“…It should be noted, however, that other investigators have reported a generalized fecundity increase in other members in the pedigrees of male HS probands, independent of the maternal or paternal line (King et al 2005;Schwartz et al 2010), and Rieger et al (2012), based on the dataset by Schwartz et al (2010), found excess fecundity in brothers of male HS. Subsequently, the data by Schwartz et al (2010) were reanalyzed by Camperio Ciani and Pellizzari (2012), highlighting, also in this dataset, a previously unnoticed larger maternal-line female fecundity. Finally, a population dynamics analysis of male HS (see Camperio Ciani et al 2008 and the section Genetic Models for Male HS below), showed a rather singular, previously unconsidered, fecundity increase in paternal aunts of heterosexuals, as compared with homosexuals.…”
Section: Human Homosexualitymentioning
confidence: 80%
“…It should be noted, however, that other investigators have reported a generalized fecundity increase in other members in the pedigrees of male HS probands, independent of the maternal or paternal line (King et al 2005;Schwartz et al 2010), and Rieger et al (2012), based on the dataset by Schwartz et al (2010), found excess fecundity in brothers of male HS. Subsequently, the data by Schwartz et al (2010) were reanalyzed by Camperio Ciani and Pellizzari (2012), highlighting, also in this dataset, a previously unnoticed larger maternal-line female fecundity. Finally, a population dynamics analysis of male HS (see Camperio Ciani et al 2008 and the section Genetic Models for Male HS below), showed a rather singular, previously unconsidered, fecundity increase in paternal aunts of heterosexuals, as compared with homosexuals.…”
Section: Human Homosexualitymentioning
confidence: 80%
“…In addition, three large studies have reported no sexual orientation-related differences in handedness (Miller et al, 2008;Rahman, Clarke, & Morera, 2009;Schwartz, Kim, Kolundzija, Rieger, & Sanders, 2010). Scholars give the impression that there is consensus for an association between non-right handedness and homosexuality yet these three studies which do not report an association are notable in their sample size and use of continuous measures of handedness.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is only modest evidence of physical differences between gay/ lesbian and heterosexual individuals suggestive of atypical sexual differentiation (e.g., Schwartz, Kim, Kolundzija, Rieger, & Sanders, 2010). The physical differences that have been found are not found consistently and have weak effect sizes, thus accounting for little of the variance in sexual orientation (Hines, 2011;LeVay, 2010).…”
Section: Introductionmentioning
confidence: 99%